2018
DOI: 10.1177/1756284818793558
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase-dependent expansion of T-regulatory cells maintains mucosal healing in ulcerative colitis

Abstract: Background:Dendritic cell (DC)-derived indolamine 2,3-dioxygenase (IDO) degrades tryptophan to kynurenine, which promotes conversion of inflammatory T cells in immunosuppressive regulatory T cells (Tregs). We analyzed the significance of the IDO:Treg axis for inducing and maintaining mucosal healing in ulcerative colitis (UC).Methods:Dextran sodium sulphate (DSS)-induced colitis in BALB/c mice (model for mucosal healing) and C57BL/6 mice (model for persistent disease) was used. Serum, fecal samples and colon-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 59 publications
2
28
0
Order By: Relevance
“…In inflamed mucosa of IBD patients, increased IDO1 activity was observed in colon epithelial cells, particularly at borders of crypt abscesses or at sites where epithelial cells flanked ulcers, suggesting involvement of the IDO1/KYN pathway in the repair process of mucosal healing. 59 In line with these observations are our recently published results 50 that indicate the importance of IDO1-dependent expansion of endogenous Tregs as a possible new therapeutic approach for the induction of mucosal healing. We demonstrated that colon-infiltrating DCs, through the production of KYN, induced expansion of Tregs that promote mucosal healing in the injured colons.…”
Section: Ido1-dependent Modulation Of Inflammatory Diseases Of the Gasupporting
confidence: 62%
See 3 more Smart Citations
“…In inflamed mucosa of IBD patients, increased IDO1 activity was observed in colon epithelial cells, particularly at borders of crypt abscesses or at sites where epithelial cells flanked ulcers, suggesting involvement of the IDO1/KYN pathway in the repair process of mucosal healing. 59 In line with these observations are our recently published results 50 that indicate the importance of IDO1-dependent expansion of endogenous Tregs as a possible new therapeutic approach for the induction of mucosal healing. We demonstrated that colon-infiltrating DCs, through the production of KYN, induced expansion of Tregs that promote mucosal healing in the injured colons.…”
Section: Ido1-dependent Modulation Of Inflammatory Diseases Of the Gasupporting
confidence: 62%
“…25,56 Tregs, in a CTLA-4 and IL-10-dependent manner, suppress activation of gut-infiltrated Th1 and Th17 cells, contributing to the attenuation of colitis. 57 We 50 and others 49,58 noticed significantly higher serum and fecal levels of KYN and higher presence of IDO-producing DCs and Tregs in the lamina propria of IBD patients compared with healthy subjects that might represent a compensatory mechanism for functional induction of tolerance in active IBD, due to the increase in absolute number of colon-infiltrating, IFN-γ-producing Th1 and IL-17-producing Th17 inflammatory cells.…”
Section: Ido1-dependent Modulation Of Inflammatory Diseases Of the Gamentioning
confidence: 85%
See 2 more Smart Citations
“…IDO1 is a major regulator of the Tryptophan (Trp) catabolism pathway that has been linked to impairment of anti-tumor immunity and tumor growth in several models (13,14). Kynurenine, which is notably produced by IDO1, is a key metabolite of this pathway that can promote selective expansion of regulatory T cells (Tregs) (15). Strikingly, we found a statistically significant increase in the kynurenine/tryptophan ratio, a robust pharmacodynamic marker of the IDO1/Kynurenine pathway (KP), between pretreatment and on-treatment plasma samples of sarcoma patients treated with Pembrolizumab.…”
Section: Introductionmentioning
confidence: 99%